1991
DOI: 10.1051/rnd:19910103
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary linseed oil and sunflower seed oil on some mechanical and metabolic parameters of isolated working rat hearts

Abstract: Summary ― The role played by membrane lipid environment on cardiac function remains poorly defined. The polyunsaturated fatty acid profile of myocardial phospholipids could be of utmost importance in the regulation of key-enzyme activities. This study was undertaken to determine whether selective incorporation of n-6 or n-3 fatty acids in membrane phospholipids might influence cardiac mechanical performances and metabolism. For 8 wk, male weanling Wistar rats were fed a semipurified diet containing eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…The phospholipid fatty acid composition was determined in cardiac homogenates as previously described [24]. The lipids were extracted according to Folch et al .…”
Section: Methodsmentioning
confidence: 99%
“…The phospholipid fatty acid composition was determined in cardiac homogenates as previously described [24]. The lipids were extracted according to Folch et al .…”
Section: Methodsmentioning
confidence: 99%
“…Animal experiments have suggested that dietary ALA, with a more efficient conversion process (54), can reduce cardiac arrhythmias in rats, but the reduction is significantly less than that induced by pure DHA or EPA (58). ALA has also been reported to reduce markedly HR in isolated working rat hearts (31). However, the level of synthesis of DHA from its precursor ALA before its incorporation in the heart is a subject of much discussion (10,12,37), depending on mammalian species and target tissues.…”
mentioning
confidence: 99%
“…Demaison and Grynberg (1991) noticed that administration of fish oil to rats increased the oxidation of palmitic acid and prevented it from accumulating in heart lipids. Mg is an element involved in the oxidation of fatty acids and also influences the integrity of cellular membranes, binding phospholipids (Shils, 1997).…”
Section: Resultsmentioning
confidence: 99%